Erk1 Positively Regulates Osteoclast Differentiation and Bone Resorptive Activity - He, Yongzheng (Public Library of Science, 2011)
The extracellular signal-regulated kinases (ERK1 and 2) are widely-expressed and they modulate proliferation, survival, differentiation, and protein synthesis in multiple cell lineages. Altered ERK1/2 signaling is found in several genetic diseases with skeletal phenotypes, including Noonan syndrome, Neurofibromatosis type 1, and Cardio-facio-cutaneous syndrome, suggesting that MEK-ERK signals regulate human skeletal development. Here, we examine the consequence of Erk1 and Erk2 disruption in multiple functions of osteoclasts, specialized macrophage/monocyte lineage-derived cells that resorb bone. We demonstrate that Erk1 positively regulates osteoclast development and bone resorptive activity, as genetic disruption of Erk1 reduced osteoclast progenitor cell numbers, compromised pit formation, and diminished M-CSF-mediated adhesion and migration. Moreover, WT mice reconstituted long-term with Erk1(−/−) bone marrow mononuclear cells (BMMNCs) demonstrated increased bone mineral density as compared to recipients transplanted with WT and Erk2(−/−) BMMNCs, implicating marrow autonomous, Erk1-dependent osteoclast function. These data demonstrate Erk1 plays an important role in osteoclast functions while providing rationale for the development of Erk1-specific inhibitors for experimental investigation and/or therapeutic modulation of aberrant osteoclast function.